Pengaruh Koneksi Politik, Kepemilikan Manajerial dan Pertumbuhan Penjualan terhadap Penghindaran Pajak - Lia Apriliani; Sartika Wulandari (J-MAS (Jurnal Manajemen dan Sains), 2023)
Companies avoid tax in order to minimize the company's tax burden by utilizing loopholes in tax regulations. The purpose of this research is to analyze the effect of political connection, manajerial ownership and sales growth on tax avoidance with 2 control variables, which are firm size and firm age. The population of this research is manufacturing companies listed on the Indonesian Stock Exchange for period 2017-2021. The number of samples used in this study were 140 samples based on the purposive sampling method. The data analysis technique in this study is quantitative analysis by using multiple linier regression method. The results of this study indicate that partially the variable managerial ownership and firm size have a positive affect on tax avoidance in sample companies, while the political connection, sales growth and firm age do not affect on tax avoidance in sample companies.